RANCANG BANGUN MONITOR STUNTING BERBASIS INTERNET OF THINGS - Rofi’i , Mohammad; Perdy Holiwi; Anggiat Winner (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2025)
Stunting is a major public health issue that affects children's growth and the quality of future generations. This study aims to design and test an Internet of Things (IoT)-based device to measure infants’ body weight, height, and head circumference, and transmit the data automatically to a web server. The research method used is research and development with a hardware and software engineering approach. The system uses an ESP32 microcontroller to process data from Load Cell and Rotary Encoder sensors, integrated with an LCD interface and Wi-Fi connectivity. The test results show that the device has a weight measurement error rate between 3.2%–3.3% and a height measurement error between 0%–3.65%, which are within acceptable limits. The transmitted data can be accessed in real-time and used to assess nutritional status based on anthropometric parameters. The implication of this research is the availability of an efficient and accurate screening tool for early stunting detection that can be applied in both primary healthcare settings and home environments.